2014
DOI: 10.2340/00015555-1704
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Case of Toxic Epidermal Necrolysis Caused by Cefozopran and Associated with Psoriasis

Abstract: Cefozopran is a fourth-generation cephem antibiotics and has a broad spectrum of antibacterial activity, inhibiting most of the gram-negative and gram-positive organisms and is used as an antibiotic agent for the empirical treatment of bacterial infections in febrile neutropenia patients (1). There have been several case reports of mild cutaneous side effects, such as exanthema, due to cefozopran, however, no severe drug eruption by cefozopran has been documented in English literature. Herein, we report the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…To our knowledge, this is the first report of drug eruption, specifically AGEP, caused by faropenem. AGEP is caused by a variety of medicines and has been reported as exemplified by antibiotics (5,7). In our patient, the apparently positive LST with faropenem confirmed the causative drug.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…To our knowledge, this is the first report of drug eruption, specifically AGEP, caused by faropenem. AGEP is caused by a variety of medicines and has been reported as exemplified by antibiotics (5,7). In our patient, the apparently positive LST with faropenem confirmed the causative drug.…”
Section: Discussionsupporting
confidence: 66%
“…1B). A lymphocyte stimulation test (LST) was performed, as described previously (5)(6)(7). 3 H-thymidine incorporation was significantly increased by the addition of 6.7×10 -6 M faropenem (corresponding to C max ) to the peripheral lymphocyte culture, with a stimulation index of 1.8 (Fig.…”
Section: Case Reportmentioning
confidence: 99%
“…This case was excluded due to limited case information (only description was in a figure legend), and no causal drug or timeline of sun exposure was provided. Two studies reported patients with past histories of psoriasis who regularly received treatments of ultraviolet-B light and experienced fatal cases of TEN, one after seven days on cefozopran and the other 16 days after starting etretinate [ 131 , 132 ]. These cases did not meet inclusion criteria because the studies did not report whether the patient received ultraviolet-B light therapy after starting the causal drug.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of drug eruption is classified into allergic and non-allergic reactions [ 13 ]. In an allergic reaction, the majority of drug eruption is mediated by type IV delayed hypersensitivity reaction, and the importance of this mechanism is proven by commonly used patch testing and lymphocyte stimulation test for the diagnosis [ 14 , 15 , 16 , 17 ]. On the basis of the pathogenesis, type IV delayed hypersensitivity reaction consists of two phases, namely, sensitization and elicitation ( Figure 1 ) [ 9 , 18 ].…”
Section: Pathogenesis Of Drug Eruptionmentioning
confidence: 99%